2006
DOI: 10.1084/jem.20051884
|View full text |Cite
|
Sign up to set email alerts
|

Roles for HLA and KIR polymorphisms in natural killer cell repertoire selection and modulation of effector function

Abstract: Interactions between killer cell immunoglobulin-like receptors (KIRs) and human leukocyte antigen (HLA) class I ligands regulate the development and response of human natural killer (NK) cells. Natural selection drove an allele-level group A KIR haplotype and the HLA-C1 ligand to unusually high frequency in the Japanese, who provide a particularly informative population for investigating the mechanisms by which KIR and HLA polymorphism influence NK cell repertoire and function. HLA class I ligands increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
643
8
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(687 citation statements)
references
References 58 publications
33
643
8
1
Order By: Relevance
“…From this, testable hypotheses can be formed about the extent to which each gene or allele, in conjunction with ligand variation, can predispose to a phenotype. For example, the cell surface expression of KIR3DL1 and the ability to recognize HLA‐Bw4 ligand vary according to allele, and hence KIR3DL1 alleles should be analysed accordingly in the disease context 25, 38, 58, 72. Similarly, polymorphism in the extracellular domain of KIR2DL1 influences the binding affinity to HLA‐C2 34, 40.…”
Section: Kir Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this, testable hypotheses can be formed about the extent to which each gene or allele, in conjunction with ligand variation, can predispose to a phenotype. For example, the cell surface expression of KIR3DL1 and the ability to recognize HLA‐Bw4 ligand vary according to allele, and hence KIR3DL1 alleles should be analysed accordingly in the disease context 25, 38, 58, 72. Similarly, polymorphism in the extracellular domain of KIR2DL1 influences the binding affinity to HLA‐C2 34, 40.…”
Section: Kir Geneticsmentioning
confidence: 99%
“…KIR3DL1*004 null allele is present at a mean frequency of 24·2% (SD 10·3) in worldwide populations 56. The frequency of cells positive for a given KIR is tightly linked to KIR gene copy number; a donor with two copies of KIR3DL1 will have a greater frequency of KIR3DL1 + NK cells than donors with only one copy,37, 38, 142 suggesting that each KIR gene copy is regulated independently. Additionally, NK cell KIR expression is related to cellular differentiation.…”
Section: Kir Gene Expressionmentioning
confidence: 99%
“…10,12,13 3DL1-mediated NK cell inhibition through Bw4 is considered a strong inhibitory interaction. 14 A number of activatory KIR (2DS1, 2DS2) also bind to HLA class I, albeit with weaker affinity and variation in the presence or absence of each can influence NK cell function. 15,16 Several studies indicate that KIRs have evolved in humans to fulfill diverse functions as a consequence of a wide range of evolutionary pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The opposing functions of activatory and inhibitory KIR is believed to reflect underlying processes of balancing and positive selection in response to pressures imposed by pathogens and coevolution with their rapidly evolving HLA class I ligands. 14,[17][18][19][20] Evidence also suggests the emergence of KIR to fulfill important roles during pregnancy [21][22][23] in which it has been shown that they influence the role of uterine NK cell in vascular remodeling during fetal trophoblast cell invasion of the deciduas. 24 As a likely consequence of these selective pressures, KIR diversity at the genetic, phenotypic and functional levels is immense.…”
Section: Introductionmentioning
confidence: 99%
“…29 The 2DS4del form prevails in KIR2DS4-positive Caucasians, 30,31 whereas the opposite is true for Oriental populations. 28,32 Yen et al 24 did not differentiate between 2DS4fl and 2DS4del alleles, so the nature of their RA-associated KIR2DS4 molecule (cell membrane-activating receptor vs soluble 2DS4del protein, possibly masking a ligand for 2DS4fl and other receptors) is not known. It therefore seems premature to speculate on the role of KIR2DS4 in the Taiwanese' susceptibility to RA.…”
mentioning
confidence: 99%